Interpersonality Communication of Writer, Character and Reader in Belles-Lettres - A. S. Komarov (Vestnik MGIMO-Universiteta)
The article is devoted to intercourse between the writer, the character and the reader, their roles in the process, the characteristics and nature of interpersonal relations between them. The author describes the two types of interpersonal relations: manipulative intercourse and communicative intercourse. Manipulative intercourse is looked upon as a process of depriving one participant of their individuality by the other. Special attention is paid to the nature, sources, and differences between these types of relations, their manifestation in belles-lettres, ways of transforming communication into manipulation.